Ionization of imidazole in the gas phase, microhydrated environments, and in aqueous solution - Jagoda-Cwiklik, Barbara; Slavíček, Petr; Cwiklik, Lukasz; Nolting, Dirk; Winter, Bernd; Jungwirth, Pavel (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2008)
Hydration of neutral and cationic imidazole is studied by means of ab initio and molecular dynamics calculations, and by photoelectron spectroscopy of the neutral species in a liquid microjet. The calculations show the importance of long range solvent polarization and of the difference between the structure of water molecules in the first shell around the neutral vs cationic species for determining vertical and adiabatic ionization potentials. The vertical ionization potential of neutral imidazole of 8.06 eV calculated using a nonequilibrium polarizable continuum model agrees well with the value of 8.26 eV obtained experimentally for an aqueous solution at pH 10.6.
Keywords: rozpouštědla; Imidazoles; voda; roztoky; Financing, Organized; Gases; Solutions; chemické modely; imidazoly; financování organizované; Solvents; Models, Chemical; plyny; Water